Contrasting effects on HIF-1alpha regulation by disease-causing pVHL mutations correlate with patterns of tumourigenesis in von Hippel-Lindau disease. - Clifford, S; Cockman, M; Smallwood, A; Mole, D; Woodward, E; Maxwell, P; Ratcliffe, P; Maher, E (2001)
The von Hippel-Lindau tumour suppressor gene product (pVHL) associates with the elongin B and C and Cul2 proteins to form a ubiquitin-ligase complex (VCBC). To date, the only VCBC substrates identified are the hypoxia-inducible factor alpha subunits (HIF-1alpha and HIF-2alpha). However, pVHL is thought to have multiple functions and the significance of HIF-1alpha and HIF-2alpha regulation for tumour suppressor activity has not been defined. VHL disease is characterized by distinct clinical subtypes. Thus haemangioblastomas (HABs) and renal cell carcinoma (RCC) but not phaeochromocytoma (PHE) occur in type 1 VHL disease. Type 2 subtypes are characterized by PHE susceptibility but differ with respect to additional tumours (type 2A, PHE+HAB but not RCC; type 2B, PHE+ HAB+RCC; type 2C, PHE only). We investigated in detail the effect of 13 naturally occurring VHL mutations (11 missense), representing each phenotypic subclass, on HIF-alpha subunit regulation. Consistent effects on pVHL function were observed for all mutations within each subclass. Mutations associated with the PHE-only phenotype (type 2C) promoted HIF-alpha ubiquitylation in vitro and demonstrated wild-type binding patterns with pVHL interacting proteins, suggesting that loss of other pVHL functions are necessary for PHE susceptibility. Mutations causing HAB susceptibility (types 1, 2A and 2B) demonstrated variable effects on HIF-alpha subunit and elongin binding, but all resulted in defective HIF-alpha regulation and loss of p220 (fibronectin) binding. All RCC-associated mutations caused complete HIF-alpha dysregulation and loss of p220 (fibronectin) binding. Our findings are consistent with impaired ability to degrade HIF-alpha subunit being required for HAB development and RCC susceptibility.